Multi-Criterion Decision Making for Planning in Internet of Things Environment - Paras Chawla , Abhinav Juneja , Sapna Juneja , Rohit Anand (International Journal of Advanced Science and Technology, 2020)
Over the recent few years, there is massive demand of internet related technologies and Internet ofThings(IOT) has emerged as a very competent source to capture meaningful business informationthrough advanced sensors. There are a lot of applications that are relying on big data and internet ofthings. Large volumes of data are being pumped from the business environments and are beingtrusted for business monitoring and control goals for various kinds of big industrial plants, trafficcontrol, retail management or even small applications. The data streams generated and maintainedusing big data are generally used for making long term decisions while IoT is used for makingdynamic decisions at faster response rate. In this paper, we have tried to present an approach tosample and rank the critical business data from the incoming data sample streams and makedecisions on the monitoring and management of the business based upon the few high ranked samplesso that the decision making is more focused towards the optimum solution of the problem. We haveused Hasse average ranking and absolute ranking for ranking the sampled data set of traffic data ofcity of Sao Paulo